Feet and Leg Traits are Moderately to Lowly Heritable in Red Angus Cattle - L. K. Giess; B. R. Jensen; R. L. Weaber; J. M. Bormann; W. A. Fiske (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:The goals of this study were to identify feet and leg indicator traits to be used in beef breed genetic evaluations and develop a scoring method that can be easily adopted by cattle producers. Description:Data were analyzed on 1,885 Red Angus cattle, and after editing, 1,720 records were used for analysis. Feet and leg phenotypes were obtained from August 2015 through September 2017 for 14 traits shown in the following table. Trained livestock evaluators collected measurements using an electronic tablet with offline data storage capabilities. Heritability estimates for all 14 traits were calculated from two different measurements of scale, the original 1-100 scale (1 and 100 are extreme, 50 is desirable), and scores truncated to a 1-9 scale (1 and 9 are extreme, 5 is desirable). Genetic parameters were estimated using maximum log likelihood procedures. The Bottom Line:Feet and leg traits are moderately to lowly heritable; however, producers can still select on traits for improved soundness. Scoring on a simpler, less granular measurement of scale (1-9) is appropriate to be used in further research.
Keywords: soundness; beef cattle; genetics